Optimal sensor placement methodology of hydraulic control system for fault diagnosis - Kong, Xiangdi; Cai, Baoping; Liu, Yonghong; Zhu, Hongmin; Liu, Yiqi; Shao, Haidong; Yang, Chao; Li, Haojie; Mo, Tianyang (Mechanical systems and signal processing, 2022)
•A sensor placement methodology of hydraulic control system is proposed.•Discrete particle swarm algorithm is applied to optimize number and position of sensors.•The proposed methodology has an efficient convergence speed and high diagnostic efficiency. During the state monitoring and fault diagnosis of hydraulic control system, different kinds of sensors are used to collect fault signals. The arrangement of a limited number of sensors in the most reasonable positions of the hydraulic system, that is, to solve the problem on the optimal placement of sensors, is the key to improving efficiency of fault diagnosis. Aiming at fault diagnosis of hydraulic control system, this paper proposes a sensor placement methodology of hydraulic control system to determine the optimal number and position of sensors based on a discrete particle swarm algorithm. First, the model of fault propagation and sensor response time is evaluated by a simulation model. Second, a discrete optimization model for sensor placement is established. Finally, a discrete particle swarm optimization algorithm is used to calculate the optimal solution for the optimal placement of sensors. In the iterative process, a Monte Carlo simulation-based comparison algorithm is used for the evaluation and comparison of particle. The simulation case of typical multi-circuit hydraulic control systems proves that the proposed method has fast convergence speed and optimization results. A real case of a subsea blowout preventer control system shows that the proposed method reduces the number of sensors and data redundancy effectively. Compared with the traditional method, the robustness of the proposed system under the optimal solution is improved.